Uniform shrub growth response to June temperature across the North Slope of Alaska. (27th March 2018) - Ackerman, Daniel E; Griffin, Daniel; Hobbie, Sarah E; Popham, Kelly; Jones, Erin; Finlay, Jacques C
Abstract: The expansion of woody shrubs in arctic tundra alters many aspects of high-latitude ecosystems, including carbon cycling and wildlife habitat. Dendroecology, the study of annual growth increments in woody plants, has shown promise in revealing how climate and environmental conditions interact with shrub growth to affect these key ecosystem properties. However, a predictive understanding of how shrub growth response to climate varies across the heterogeneous landscape remains elusive. Here we use individual-based mixed effects modeling to analyze 19 624 annual growth ring measurements in the stems of Salix pulchra (Cham.), a rapidly expanding deciduous shrub. Stem samples were collected at six sites throughout the North Slope of Alaska. Sites spanned four landscapes that varied in time since glaciation and hence in soil properties, such as nutrient availability, that we expected would modulate shrub growth response to climate. Ring growth was remarkably coherent among sites and responded positively to mean June temperature. The strength of this climate response varied slightly among glacial landscapes, but in contrast to expectations, this variability was not systematically correlated with landscape age. Additionally, shrubs at all sites exhibited diminishing marginal growth gains in response to increasing temperatures, indicative of alternative growth limiting mechanisms in particularly warm years, such as temperature-induced moisture limitation. Our results reveal a regionally-coherent and robust shrub growth response to early season growing temperature, with local soil properties contributing only a minor influence on shrub growth. Our conclusions strengthen predictions of changes to wildlife habitat and improve the representation of tundra vegetation dynamics in earth systems models in response to future arctic warming.